Advancing local food systems despite deep federal budget cuts: An example from Silicon Valley, California, USA - Chen, Susan; Vollmer, Laura; Sotnik, Garry; Diekmann, Lucy; Bacon, Christopher (Journal of Agriculture, Food Systems, and Community Development, 2025)
Summary: Abrupt federal budget cuts and the elimination of select federal programs that support agroecology and value chain coordination have disrupted small-scale food producers and community stakeholders throughout the United States. In April 2025, regional food systems stakeholders in California’s Silicon Valley convened to discuss ways to sustain agroecology and food justice programming in the face of federal funding cuts. Two themes emerged: (1) Regional governments can continue to support entities through local food systems plans; and/or (2) Food system organizations can be equipped with skills to organize for local policy changes. In the long term, sustainable and localized initiatives are warranted.